Numerical simulation of hydraulic bulging using uniaxial and biaxial flow curves and different yield criteria. (November 2019) - Prakash, Ved; Kumar, D. Ravi; Merklein, Marion; Hagenah, Hinnerk
Abstract: In sheet metal forming industry, finite element analysis has become a necessary step before actual production of the parts. It helps in the improvement of part quality as well reduces the effort applied in experimental trials. However, the success of finite element simulation mainly depends on the constitutive model used for defining the plastic deformation behaviour of the sheet material. Material characterization in biaxial stress state helps in selecting advanced constitutive models in numerical simulations. In this work, aluminium alloy AA5083 sheet material is characterized in uniaxial and biaxial tension conditions. Hydraulic bulge tests are performed to obtain the flow curves and material properties which are then used to find the coefficients in different yield criteria. These coefficients and the flow curves, fitted using different work hardening laws, are used in finite element simulation of the hydraulic bulge test and the results are validated by experiments.